Nazwy wiosennych kwiatów według polskich leksykografów - "fiołek" = Names of Spring Flowers According to Polish Lexicographers - "Violet" - Migdał, Jolanta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article discusses the way in which Polish lexicographers present the name of the spring flower "violet", what the origin of this term was, what the history of this name in the Polish language was. The study, which is based on the analysis of dictionaries, is limited to the picture delineated in the etymological dictionaries of the Polish language and in the dictionaries of general Polish, both historical and contemporary.
Keywords: leksykografia polska; kwiat; fiołek; Polish lexicography; flower; violet